Antioxidative peptides of hydrolysate prepared from fish skin gelatin using ginger protease activate antioxidant response element-mediated gene transcription in IPEC-J2 cells. (December 2018) - Zheng, Liufeng; Yu, Huichao; Wei, Hongkui; Xing, Qian; Zou, Yi; Zhou, Yuanfei; Peng, Jian
Graphical abstract: Highlights: Ginger protease effectively hydrolyzed gelatin from fish skin. FSGH obtained by ginger protease showed the strongest antioxidant capacities. Antioxidant fractions were isolated from FSGH. Two main types of peptides were identified: Gly-Pro-Y and X-Hyp-Gly-type tripeptides. Gly-Pro-Ala showed the highest ARE–luciferase activity in IPEC-J2 cells. Abstract: Excess production of reactive oxygen species (ROS) causes oxidative stress, which is associated with oxidative damage and a number of human chronic diseases. Here, novel antioxidant hydrolysates were obtained from fish skin, pig skin, pig bone and bovine skin gelatins using ginger protease, and were compared with those produced using pepsin-pancreatin. Ginger protease could hydrolyze the gelatin from fish skin to peptides with low average molecular weights (<690 Da) more efficiently than that from pig skin, pig bone and bovine skin. All gelatin hydrolysates showed higher antioxidative activities than non-hydrolysed gelatins. Especially, fish skin gelatin hydrolysate (FSGH) obtained using ginger protease exhibited the highest degree of hydrolysis (13.08%) and antioxidant activity towards DPPH radical (97.21%) and lipid peroxidation (48.46%). The FSGH was then separated into three fractions by ultrafiltration. The fraction with a molecular weight below 1000 Da demonstrated the strongest scavenging capacity for DPPH and hydroxyl radicals and inhibitory effect on lipid peroxidation. Further HPLC-ESI-QqQ-MS results revealed that this fraction mainly included two types of peptides: Gly-Pro-Y-type and X-Hyp-Gly-type tripeptides. The ARE-luciferase activity of a selection of the identified oligopeptides was examined using the IPEC-J2 cell model. The most active peptide was Gly-Pro-Ala, which showed an approximately 2.5-fold increase in ARE-luciferase activity. Additionally, Gly-Pro-Ala (0–2.5 mg/mL) activated the expression of ARE-driven antioxidant enzyme genes in a dose dependent manner, and subsequently suppressed the H2 O2 -induced intracellular ROS production. Overall, our results demonstrate that FSGH prepared using ginger protease could serve as a source of peptides with high antioxidative activities.